SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMPN 1 ULU BELU - Java Aminatuzzahro; Taqwatul Uliyah; Nur Widiastuti; Ami Latifah (UNISAN JURNAL, 2023)
This study aimed to investigate how academic supervision conducted by the principal can improve teacher performance at SMPN 1 Ulu Belu. The study used a qualitative approach with a single case study method. Data was collected through interviews with the principal and several teachers at SMPN 1 Ulu Belu, as well as observation of the academic supervision practices conducted by the principal. The collected data was analyzed using descriptive analysis techniques. The results showed that academic supervision conducted by the principal plays an important role in improving teacher performance at SMPN 1 Ulu Belu. The principal acts as a facilitator, motivator, and professional developer of teachers. The impact of academic supervision on teacher performance includes increasing motivation and teacher performance, improving the quality of learning, enhancing teacher skills and abilities, improving the relationship between teachers and the principal, and improving the overall quality of education at SMPN 1 Ulu Belu. This study concludes that academic supervision conducted by the principal can be an effective strategy in improving teacher performance at SMPN 1 Ulu Belu.